Penggunaan Teknologi Informasi dalam Membentuk Citra dan Branding dalam Dakwah - Nur Hidayatul Istiqomah; Siti Fatimah; Zakariya A. Fahmi (ASWALALITA: Journal of Da'wah Management, 2023)
This research examines the use of information technology as a strategic tool in shaping the image and branding in Islamic preaching (Dakwah). The study aims to investigate how information technology, including social media, websites, and other digital platforms, has influenced the way Dakwah messages are delivered and received by the public. We also explore the impact of information technology on shaping perceptions and the image of Dakwah organizations, as well as how this contributes to efforts to enhance public appeal and trust. The library research method is employed to gather relevant literature, analyze trends, and formulate arguments in this study. Findings from the literature provide deep insights into how information technology has become a key factor in defining the brand identity of Dakwah, reaching a broader audience, and building stronger relationships between preachers and the community. The results of this research are expected to provide a better understanding of the role of information technology in the context of Dakwah and offer guidance to Dakwah organizations and preachers on how to use technology wisely to improve their image and branding. Additionally, this study will also address challenges and obstacles related to the use of information technology in Dakwah and its potential future impacts.